2019
DOI: 10.1093/bioinformatics/btz254
|View full text |Cite
|
Sign up to set email alerts
|

A learning-based framework for miRNA-disease association identification using neural networks

Abstract: Motivation A microRNA (miRNA) is a type of non-coding RNA, which plays important roles in many biological processes. Lots of studies have shown that miRNAs are implicated in human diseases, indicating that miRNAs might be potential biomarkers for various types of diseases. Therefore, it is important to reveal the relationships between miRNAs and diseases/phenotypes. Results We propose a novel learning-based framework, MDA-CNN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 152 publications
(50 citation statements)
references
References 48 publications
0
50
0
Order By: Relevance
“…The top 3 gene classes are protein coding, pseudogene, and lncRNA genes. Although many studies have shown that non-coding RNAs play key roles in the complex regulatory networks in cell system, most of their functions are still missing (Cheng et al, 2018a;Cheng et al, 2018d;Peng et al, 2019b). Further computational methods and biological experiments are still needed to understand these unknown markers, such as using phynotypes, ontologies, deep learning methods, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The top 3 gene classes are protein coding, pseudogene, and lncRNA genes. Although many studies have shown that non-coding RNAs play key roles in the complex regulatory networks in cell system, most of their functions are still missing (Cheng et al, 2018a;Cheng et al, 2018d;Peng et al, 2019b). Further computational methods and biological experiments are still needed to understand these unknown markers, such as using phynotypes, ontologies, deep learning methods, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, this approach will lead to class-imbalance problem since the number of known circRNAs is much fewer than the number of unknown circRNAs. is phenomenon has also been widely discussed in identifying disease-related genes, miRNAs and lncRNAs [47,[51][52][53]. erefore, it is not scienti c to regard all unknown genes as negative samples.…”
Section: Complexitymentioning
confidence: 99%
“…They provide important data support for circRNA–disease association analyses. Some methods have been proposed to provide the most promising disease-related biomarkers, including those involving lncRNAs (Chen et al, 2015; Gu et al, 2017; Cheng et al, 2018a; Cheng et al, 2019), miRNAs (Peng et al, 2019b; Shao et al, 2018), genes (Cheng et al, 2016; Hu et al, 2019; Peng et al, 2019a), and drugs (Jiang et al, 2017; Zhang et al, 2017), for further experimental validation. These methods can decrease the time and cost of biological experiments.…”
Section: Introductionmentioning
confidence: 99%